Performance Analysis of Horizontal Shaft Wind Turbine Through Blade Design Modification - Siahaan, Enzo W B; Sidabutar, Rotama Arifin; Sitanggang, Hodmiantua (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The objective of this study is to investigate the performance of a horizontal shaft wind turbine model with variations in blade shapes. The focus of the research lies in examining the impact of different blade shapes, specifically the curved shape, inverted linear taper, and rectangular shape measuring 8 cm x 20 cm at a 200 tilt angle. The experiments are conducted at various wind speeds: 7, 8, 9, 10, and 11 m/s. The findings reveal that changes in blade shape significantly influence the operation of the horizontal shaft wind turbine. The Brake Horse Power (BHP) reaches its maximum with a rectangular blade shape, achieving 1.1 watts at a wind speed of 11 m/s and a corresponding torque of 0.0221 Nm. Additionally, the highest efficiency is attained with the rectangular blade shape at a wind speed of 7 m/s, reaching 21%.